Peran Sel T Memori dalam Pengendalian Pandemi Covid-19 - Kusmardi; Ramadhian N, Dimas; Pratomo, Irandi P; Tedjo, Aryo (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2021)
ABSTRACTEvaluation of changes in antibody orders is a common exclusion in vaccination strategies because of the method ofanalysis. The fact that protection by antibodies produced by the Severe Acute Respiratory Syndrome Coronavirus-2(Sars-Cov-2) infection both naturally and through vaccines will decrease in less than one year, is a challenge for acountry with a large population like Indonesia to run its vaccination program. The main challenge is whether thevaccination strategy adopted will overcome the vaccine barrier and the race between the rate of vaccination and therate of viral mutation and antibody reduction. In addition to antibodies, the adaptive immune system is also run by Tcells that are included in the cell-mediated immune system (CMI) group. In patients with asymptomatic or mildsymptoms of Coronavirus 2019 (Covid-19), T and CMI responses are known to appear in some patients who are notknown to have been exposed to Sars-Cov-2 before. This evidence suggests that the adaptive catastrophe for SarsCov-2 has been acquired by ordering memory T cells and may last longer than previously thought. For countries withlarge populations, this will certainly help overcome the limitations of vaccines and the time needed to implement theirvaccination strategies.